Effect of Different Bleaching Methods on Monomer Release from Aged Microhybrid and Nanohybrid Resin Composites - Siavash Abdollahpour; Tarane Estedlal; Nasim Chiniforush; Niyousha Rafeie; Nariman Nikparto; Mahdi Abbasi; Ladan Ranjbar Omrani (International Journal of Dentistry)
Introduction. Recently, the application of laser-assisted bleaching has increased in dental practice. This method might affect the physical and chemical properties of resin composite and its monomer release. This study aimed to evaluate the effect of in-office, at-home, and laser-assisted bleaching on the monomer release (bisphenol A diglycidyl dimethacrylate (BisGMA), triethylene glycol dimethacrylate (TEGDMA), and urethane dimethacrylate (UDMA)) from aged nanohybrid (Grandio, Voco) and microhybrid (Clearfil AP-X Esthetics, Kuraray) resin composites. Methods. Thirty-two samples of each composite were prepared. The samples underwent aging procedure with UV light at 65°C for 100 hr. The samples were divided into 4 groups: OB: conventional in-office bleaching with Opalescence Boost PF 40% gel; HB: home bleaching with Opalescence PF 15% gel; LB: bleaching with JW Power bleaching gel followed by diode laser application; and C: control group without bleaching. Then, the samples were immersed in a solution containing 75% ethanol + 25% distilled water. The medium was renewed after 8, 16, 24 hr, and 7 days and was analyzed using high-performance liquid chromatography method to evaluate the monomer release. The data were analyzed using Two-way ANOVA and Post hoc Tukey test. Results. The bleaching method had no effect on TEGDMA and BisGMA release in both composites while it affected UDMA release in nanohybrid composite; UDMA release was significantly higher in LB compared to control and also higher in OB and LB compared to HB. No difference was observed in the microhybrid composite in this regard. Conclusion. Laser-assisted bleaching did not affect monomer release from microhybrid composite while it increased UDMA release from nanohybrid composite. The bleaching method had no effect on TEGDMA and BisGMA release.